Comparative video annotation and visual literacy: performance analysis of Rina Yerushalmi's theatre language. Issue 1 (2nd January 2021) - Aronson-Lehavi, Sharon; Skop, Natan; Via Dorembus, Yael
ABSTRACT: The growing availability of video recordings of theatre performances, a phenomenon that has increased during Covid19 as theatres worldwide share videos online, affects the field of theatre and performance studies. Video recordings of theatre performances are archival documents and mediated 'performance texts' that enable new kinds of performance analysis and studying bodily practices. This paper addresses annotative methodologies as part of the research project, 'The Art of Adaptation: The Theatre of Rina Yerushalmi and the Itim Ensemble.' The project studies the video archive of the ensemble, which includes recordings of full productions and rehearsal processes. We discuss three kinds of digital comparative annotative methodologies to show how annotation can be used as a research tool for performance analysis: (1) Accumulative annotation: analysis of multi-layered theatrical sequences, revealing theatrical moments in their multiplicity. (2) Annotation of different scenes in a corpus of works: juxtaposing scenes from different productions enables the articulation of repetitive performative patterns, embodied practices, and visual images that construct a theatre language. (3) Annotation of the same scene at different phases: juxtaposing video recordings of the same scene at different moments of its development reveals nuanced sets of information about directorial choices, acting, movement, duration, and more.